Hubungan Toleransi Stres dengan Kecenderungan Binge Eating Disorder dan Obesitas - Kurniawati, Diah; Soewadi, Soewadi; Winarso, Mariyono Sedyo (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2009)
Please refer to the file